Anthropogenic Infection of Domestic Cats With SARS-CoV-2 Alpha Variant B.1.1.7 Lineage in Buenos Aires - Pecora, Andrea; Malacari, Dario Amilcar; Mozgovoj, Marina Valeria; Díaz, María de los Ángeles; Peralta, Andrea Verónica; Cacciabue, Marco; Puebla, Andrea Fabiana; Carusso, Cristian; Mundo, Silvia Leonor; Gonzalez Lopez Ledesma, María Mora; Gamarnik, Andrea Vanesa; Rinaldi, Osvaldo; et al. (Frontiers in Veterinary Science, 2022)
SARS-CoV-2 reverse zoonosis, particularly to domestic animals, and the potential role of infected animals in perpetuating the spread of the virus is an issue of increasing concern. In this case report, we identified the natural infection of two cats by SARS-CoV-2, in Argentina, whose owner had been previously infected by SARS-CoV-2. Viral genetic material was detected in feline oropharyngeal (OP) and rectal (R) swab by RT-qPCR, and sequence analysis revealed that the virus infecting the owner and one cat were genetically similar. The alpha variant (B.1.1.7 lineage) was identified with a unique additional mutation, strongly suggesting human-to-cat route of transmission. This study reinforces the One Health concept and the importance of integrating human, animal, and environmental perspectives to promptly address relevant health issues.